Prognostic Impacts of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers in Acute Coronary Syndrome Patients Without Heart Failure - Chen, Runzhen; Liu, Chen; Zhou, Peng; Li, Jiannan; Zhou, Jinying; Wang, Ying; Zhao, Xiaoxiao; Chen, Yi; Yan, Shaodi; Song, Li; Zhao, Hanjun; Yan, Hongbing (Frontiers in Pharmacology, 2022)
Background: Despite the recommendations from mainstream guidelines, the use of angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blockers (ARB) for acute coronary syndrome (ACS) patients without heart failure (HF) is controversial, as its evidence is lacking in the era of reperfusion and intensive secondary preventions. This study aimed to investigate the impacts of ACEI/ARB on outcomes of ACS patients without HF treated by percutaneous coronary intervention (PCI). Methods: A total of 2,397 non-HF ACS patients treated by PCI were retrospectively recruited. Prognostic impacts of ACEI/ARB were assessed by unadjusted analysis, followed by propensity score matching (PSM) and propensity score matching weight (PSMW) analysis to control the between-group differences. The primary outcome was a composite of all-cause death and recurrent myocardial infarction (MI). Results: Among the included patients, 1,805 (75.3%) were prescribed with ACEI/ARB at discharge. The median follow-up time was 727 (433–2016) days, with 129 (5.4%) primary endpoint events, consisting of 55 (2.3%) cases of all-cause death and 74 (3.1%) cases of recurrent MI. The use of ACEI/ARB was not associated with significant risk reduction of primary endpoint events in unadjusted analysis (hazard ratio [HR]: 0.95, 95% confidence interval [CI]: 0.64–1.39, p = 0.779), PSM analysis (HR: 0.94, 95% CI: 0.60–1.47, p = 0.784), and PSMW analysis (HR: 0.91, 95% CI: 0.55–1.49, p = 0.704). Similar results were observed for secondary outcomes of all-cause death, cardiac death, and recurrent MI. Conclusion: For ACS patients without HF, the use of ACEI/ARB was not associated with lower risk of death or recurrent MI after PCI.